Delayed effects of radiation exposure in a C57L/J mouse model of partial body irradiation with 2.5% bone marrow shielding - Beach, Tyler; Bakke, James; McDonald, J. Tyson; Riccio, Edward; Javitz, Harold S.; Nishita, Denise; Kapur, Shweta; Bunin, Deborah I.; Chang, Polly Y. (Frontiers in Public Health, 2024)
Introduction Mouse models of radiation injury are critical to the development of medical countermeasures (MCMs) against radiation. Now that MCMs against hematopoietic acute radiation syndrome (H-ARS) have achieved regulatory approval, attention is shifting to develop MCMs against the adverse effects of gastrointestinal acute radiation syndrome (GI-ARS) and delayed effects of acute radiation exposure (DEARE). The C57L/J mouse model of partial body irradiation (PBI) with 2.5% bone marrow shielding (BM2.5) is being leveraged to examine both GI-ARS and DEARE effects. Within days of PBI, mice may develop H- and GI-ARS followed several months later by DEARE as a multi-organ injury, which typically involves the lung and kidney (L- and K-DEARE, respectively). The objective of this manuscript is to describe the dose response relationship and progression of radiation injury in the C57L/J mouse and to evaluate its suitability for use in DEARE MCM testing. Materials and methods In two separate studies conducted over 2 years, male and female C57L/J mice were exposed to PBI BM2.5 with one hindlimb shielded from radiation, representing 2.5% bone marrow shielding/sparing. Mice were X-ray irradiated at doses ranging from 9 to 13 Gy at 10 to 12 weeks of age for the purposes of assessing ARS survival at 30 days and DEARE survival at 182 days post-irradiation. Clinical indicators of ARS and DEARE were determined by clinical observations, body weights, hematology, clinical chemistry, magnetic resonance imaging (MRI) of lung, and histopathology of selected tissues. Results C57L/J mice developed canonical ARS responses of hematopoietic atrophy and gastrointestinal injury resulting in dose dependent mortality at doses ≥11 Gy between 1- and 15-days post-irradiation. In animals that survived ARS, DEARE associated mortality occurred in dose dependent fashion at ≥9 Gy for both sexes between 60- and 159-days post-irradiation with histopathology examinations indicating lung injury as the primary cause of death in moribund animals. Conclusion The PBI BM2.5 C57L/J mouse model reliably produced known H- and GI-ARS effects at doses greater than those resulting in DEARE effects. Because of this, the C57L/J mouse can be used to test MCMs against L-DEARE injury, while avoiding ARS associated mortality.